RILEM Recommendations for the Prevention of Damage by Alkali-Aggregate Reactions in New Concrete Structures State-of-the-Art Report of the RILEM Technical Committee 219-ACS - Nixon, Philip J.; Sims, Ian.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This book contains the full set of RILEM Recommendations which have been produced to enable engineers, specifiers and testing houses to design and produce concrete which will not suffer damage arising from alkali reactions in the concrete. There are five recommended test methods for aggregates (designated AAR-1 to AAR-5), and an overall recommendation which describes how these should be used to enable a comprehensive aggregate assessment (AAR-0). Additionally, there are two Recommended International Specifications for concrete (AAR-7.1 & 7.2) and a Preliminary International Specification for dams and other hydro structures (AAR-7.3), which describe how the aggregate assessment can be combined with other measures in the design of the concrete to produce a concrete with a minimised risk of developing damage from alkali-aggregate reactions.
Introduction, by Philip J Nixon & Ian Sims -- RILEM Recommended Test Method: AAR-0, Outline Guide to the Use of RILEM Methods in the Assessment of the Alkali-Reactivity Potential of Aggregates -- RILEM Recommended Test Method: AAR-1.1, Detection of potential alkali-reactivity, Part 1: Petrographic Examination Method -- RILEM Recommended Test Method: AAR-2, Detection of potential alkali-reactivity, Accelerated Mortar-bar Test Method for Aggregates -- RILEM Recommended Test Method: AAR-3, Detection of potential alkali-reactivity, 38°C Test Method for Aggregate Combinations using Concrete Prisms -- RILEM Recommended Test Method: AAR-4.1, Detection of potential alkali-reactivity, 60°C Test Method for Aggregate Combinations using Concrete Prisms -- RILEM Recommended Test Method: AAR-5, Detection of potential alkali-reactivity, Rapid Preliminary Screening Test for Carbonate Aggregates -- RILEM Recommended Specification: AAR-7.1, International Specification to Minimise Damage from Alkali Reactions in Concrete, Part 1: Alkali-Silica Reaction -- RILEM Recommended Specification: AAR-7.2, International Specification to Minimise Damage from Alkali Reactions in Concrete, Part 2: Alkali-Carbonate Reaction -- RILEM Recommended Specification: AAR-7.3, Preliminary International Specification to Minimise Damage from Alkali Reactions in Concrete, Part 3: Concrete Dams and Other Hydro Structures.
Keywords: Building materials; Geochemistry; Building Materials; Structural Materials; Geochemistry